A binder-free δ-MnO2@reduced graphene oxide composite film as a bi-functional electrode for aqueous rechargeable sodium-ion batteries and hybrid capacitive deionization. (19th April 2022) - Wang, Jun; Zhang, Daile; Hu, Xiaomin; Sun, Ting
Abstract : The freestanding δ-MnO2 @rGO/CC electrode exhibits stable operation performance for both ASIBs and HCDI. Abstract : Hybrid capacitive deionization (HCDI), a promising desalination process using pairs of electrodes to obtain fresh water, has an attractive advantage of a low driving voltage. This unique character makes it fully suitable for self-powered applications using aqueous batteries. In this study, δ-MnO2 @reduced graphene oxide/carbon cloth (δ-MnO2 @rGO/CC) is synthesized by an in situ method with carbon cloth as the current collector and reduced graphene as the conducting interconnection. The MnO2 nanoparticles are intimately grown on the rGO/CC matrix and a free-standing electrode is obtained. Consequently, an integrated system with a rechargeable aqueous sodium-ion battery (ASIB) and a HCDI unit is fabricated for simultaneous energy storage and deionization. The aqueous battery is composed of δ-MnO2 @rGO/CC and activated carbon (AC) as the cathode and anode, respectively, and demonstrates a charge capacity of 77.8 mA h g −1 at a current density of 50 mA g −1, and its capacitance retention at a current density of 1000 mA g −1 is close to 97% after 1000 cycles. In addition, the δ-MnO2 @rGO/CC electrode also shows excellent deionization performance with an adsorption capacity of 19.8 mg g −1 in 10 mM NaCl solution at an applied voltage of 1.2 V. These results indicate that the δ-MnO2 @rGO/CC film is suitable for both HCDI and ASIBs.